IMPACT OF MEDIA IN VOCABULARY LEARNING AND TEACHING-LEARNING SETTINGS: A QUASI-EXPERIMENT IN ITALIAN AS HERITAGE LANGUAGE CLASSES (ItalianoLinguadue, 2021)
Heritage language classes comprise a favorable environment for the application of innovative methods sustained by new technologies for foreign learning acquisition. This preliminary study describes an experiment in classes of Italian as heritage language in Germany. The involved teachers employ, during the input-phase, didactical videos as opposed to traditional written material on paper. Through a small-N quantitative analysis, the groups taught by videos demonstrate a lexical improvement marginally higher than the groups taught by paper. From the qualitative analysis, significant changes in the learning environment emerge: in the groups taught by videos, higher interactions were registered and the learning process showed numerous elaborations (from an audiovisual input to written notes, which are rewritten in the working sheets). The observations confirm multifactorial implications within the didactical setting (Calvani & Vivanet, 2014) previously never studied within heritage languages classes in Germany. Impatto dei media nell’apprendimento del vocabolario e nel setting di insegnamento-apprendimento: un esperimento in classi di italiano come lingua d’origineLe classi di lingua d’origine offrono un ambiente particolarmente favorevole per l’applicazione di nuove tecnologie didattiche. Questo studio preliminare descrive un esperimento in classi di italiano come lingua d’origine in Germania dove gli insegnanti hanno usato video didattici in sostituzione di materiali cartacei tradizionali nella fase di introduzione delle informazioni. Nonostante un campione ristretto l’analisi quantitativa mostra che i gruppi che hanno fatto ricorso ai video registrano un apprendimento del lessico leggermente migliore dei gruppi che si sono basati sulla lettura. L’analisi qualitativa dimostra che l’apprendimento avviene in modo notevolmente diverso: nei gruppi che ricevono istruzioni attraverso i video le interazioni sono maggiori e il processo di apprendimento passa per numerose elaborazioni (da input audiovisivo a appunti scritti, per venire poi nuovamente trascritto nei fogli di lavoro). L’osservazione conferma l’esistenza di conseguenze multifattoriali delle tecnologie sul setting didattico (Calvani & Vivanet, 2014) anche in un ambiente mai precedentemente analizzato sperimentalmente come le classi di lingua d’origine in Germania.